2019
DOI: 10.1002/smll.201904918
|View full text |Cite
|
Sign up to set email alerts
|

Laser‐Assisted Lattice Recovery of Graphene by Carbon Nanodot Incorporation

Abstract: Producing highly oriented graphene is a major challenge that constrains graphene from fulfilling its full potential in technological applications. The exciting properties of graphene are impeded in practical bulk materials due to lattice imperfections that hinder charge mobility. A simple method to improve the structural integrity of graphene by utilizing laser irradiation on a composite of carbon nanodots (CNDs) and 3D graphene is presented. The CNDs attach themselves to defect sites in the graphene sheets an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 61 publications
0
13
0
Order By: Relevance
“…The carbon composite electrodes for the high‐frequency SCs were developed mostly with the graphene electrodes. [ 102–104 ] Since the graphene has advantages such as high electrical conductivity, a large specific surface area, and a 2D layered structure, it can serve as an excellent template for carbon composite materials, leading to synergistic effects. The graphene/amorphous carbon composite was synthesized by using Ni foil via ambient‐pressure CVD.…”
Section: Electrodesmentioning
confidence: 99%
See 3 more Smart Citations
“…The carbon composite electrodes for the high‐frequency SCs were developed mostly with the graphene electrodes. [ 102–104 ] Since the graphene has advantages such as high electrical conductivity, a large specific surface area, and a 2D layered structure, it can serve as an excellent template for carbon composite materials, leading to synergistic effects. The graphene/amorphous carbon composite was synthesized by using Ni foil via ambient‐pressure CVD.…”
Section: Electrodesmentioning
confidence: 99%
“…The rGO/CNT‐composite‐based SC was tested with an ionic liquid, 1‐ethyl‐3‐methylimidazolium tetrafluoroborate (EMImBF 4 ), exhibiting the moderate frequency response with an impedance phase angle of −64.4° at 120 Hz, a relaxation time constant of 2.08 ms, and a wide voltage window of 4 V. A reduced graphene oxide/carbon nanodot (rGO/CND) composite was synthesized by the laser‐assisted graphitization process. [ 104 ] The laser‐induced thermal reaction ablated the defective carbon fragments into the plasma and formed CC bonds among the neighboring carbons of the CND and rGO. The integrated merging of the reduced CND with rGO formed a continuous 3D extension of the graphene substrate patched by the CNDs.…”
Section: Electrodesmentioning
confidence: 99%
See 2 more Smart Citations
“…Building on this, we have shown that CNDs also serve to patch defects in laser-reduced GO resulting in higher surface areas and conductivities. [52,53] The addition of CNDs leads to a 130% increase in the active surface area. Compared to laser-reduced GO, the electrical conductivity grows by about ten times.…”
Section: Carbon Nanodots (Cnds) and Graphene Quantum Dots (Gqds)mentioning
confidence: 99%